What works in citizenship and values education: Attitudes of high school leavers towards the Itorero training in post-genocide Rwanda - Nzahabwanayo, S.; Divala, J.J. (South African Journal of Higher Education, 2019)
This piece of research contributes to the existing literature on citizenship and values education practices in post-conflict contexts. It set out to investigate ways in which high school leavers (HSLs) appreciate Itorero– a non-formal citizenship and values education platform in post-genocide Rwanda. The purpose of the study was also to establish the best predictor of the success of Itorero training according to HSLs’ perceptions. The research to be reported here used a survey questionnaire and focus groups with HSLs. It is revealed that while HSLs are happy with the content, they seem to be immensely displeased with the quality of trainers, organization and training environment. The article also shows that the factor ‘trainers’ consistutes the best predictor of the success of Itorero. This finding raises serious concerns because Itorero trainers are seen as deficient in number of ways. The article raises the question of trainers’ preparation in citizenship and values education. We argue that there is a tendency to neglect this aspect and assume that everyonecan contribute to citizenship and values education. We maintain that the quality of trainers is critical for optimal results in citizenship and values education.